PENELUSURAN LULUSAN PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS TERBUKA - Lis Setiawati (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2010)
A survey study on the graduates apprenticeship was conducted by the tracer study team of The Faculty of Teachers Training and Educational Sciencies, Universitas Terbuka in 2008. The graduates consisted of them of 10 programs, one of which was the Bahasa Indonesia program. This study was aimed to collect data on graduates profile which was gender, age, current profession, achievement enchanced skills and qualification especially in language and ICT skills. The study also collected data on the graduates perception about the quality of academic services during their study. A series of interview were conducted and some questionnairs were distributed to the respondents, including the graduates and their supervisor. The results of data analysis revealed the respondents consist of 34 males and 48 females, and their ages range from 31 to 60 years old. The current profession consisted of 67 teachers, the rest of them were lecturers, head masters, vice headmasters, administrators, and school supervisors. Their incomes varied from 1 to 5 million rupiahs. Thirty of 82 respondents informed that they received awards, such as Satya Lencana Karya Satya. All of the respondents indicated that their communication skills in Bahasa Indonesia were very well enchanced. In addition, sixty two of 82 respondents reported that they had average level in English competencies and ICT skills. The data analysis revealed that all the respondents indicated high level of satisfaction toward the academic services of the quality of learning assessment however they were not satisfaction toward tutorials of any form. These study results can be able to use as the valuable input for program and services improvement, especially for academic services affairs.